The Relationship between Parenting Patterns and Bullying Behavior in Class XI Adolescents at SMA PGRI 4 Jakarta - Qalbia Rahmah, Syifa; Puspita Handayani, Rosia; Utami, Balqis (International Journal of Social Science, Education, Communication and Economics, 2024)
This quantitative research aims to find out hThe relationship between parenting styles and bullying behavior in class XI teenagers at SMA PGRI 4 Jakarta. The population in this study were students at SMA PGRI 4 Jakarta, which were teenagers. The number of respondents for this research was 104 respondents. The data collection technique used was simple random sampling. The data processing method in this research uses the Bivariate Correlation data analysis technique in the SPSS 22.0 For Windows program. From this research, it was concluded that there was a negative relationship between parenting patterns and bullying behavior at SMA PGRI 4 Jakarta with the moderate bullying category, a correlation coefficient (r) of -0.195 with p = 0.047 was obtained. This means that the worse the parenting pattern provided by parents, the higher the chance of bullying behavior at SMA PGRI 4 Jakarta.